Strategic Implementation of Pre-Employment Training Programs For New Employees at PT PLN (Persero) - Dewi Arianingrum, Meira; Ma’arif, M. Syamsul; Suhendi, Suhendi (Asian Journal of Social and Humanities, 2024)
The availability of professional and trained human resources is the key to the success of a company. However, it is unfortunate when employees who have received a training program actually resign from work. This is what happened in the PLN work environment. The mental readiness factor and the training program are not as expected to be the cause for new employees. This study aims to evaluate the implementation of pre-service learning for new employee candidates of PT PLN (Persero) and find out future implementation strategies. The research method uses mixed methods, namely quantitative and qualitative. This research uses the Kirkpatrick level I approach with data processing techniques using the Customer Satisfaction Index and Importance Performance Analysis methods, as well as the Eckenrode method. The results show that the strength level of the implementation of the pre-service training program shows very good results because the training program provided by company management provides useful value to support work activities. Furthermore, this pre-service training program is considered effective because it has provided a very high level of satisfaction for employees. Meanwhile, the factor that causes employees to resign from their jobs is because there is still a mismatch between training and the reality of work practices in the field. So the future strategy to retain new employees is to strengthen the mentorship program, strengthen the character of prospective new employees, and update content, and career development.